Karakteristik Anak Leukemia Limfoblastik Akut yang Menjalani Kemoterapi - Safiyah Kamilah; Mayetti Mayetti; Deswita Deswita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the characteristics of children with acute lymphoblastic leukemia undergoing chemotherapy at Dr. M. Djamil Padang. This type of research is descriptive-analytic with a cross-sectional approach. The results showed that the characteristics of the respondents of children with acute lymphoblastic leukemia were mainly school aged (6-12 years), totaling 16 respondents with a percentage of (72.7%). The characteristics of respondents based on gender are primarily male, namely as many as 15 respondents with a ratio of (68.15%). The features of respondents based on nutritional status were divided into three categories, including undernutrition which amounted to 3 respondents with a percentage (13.65%). Normal nutrition amounted to 12 respondents with a rate (of 54.55%), and excess food amounted to 7 respondents with a percentage (of 31.85 %). In conclusion, the description of the characteristics of children with acute lymphoblastic leukemia undergoing chemotherapy is that the majority are school-age children (6-12 years), male, and in average (reasonable) nutritional status. Keywords: Children, Chemotherapy, Leukemia